Clinical risk reclassification at 10 years. (20th November 2017) - Cook, Nancy R.; Demler, Olga V.; Paynter, Nina P.
Abstract : Three papers in this issue focus on the role of calibration in model fit statistics, including the net reclassification improvement (NRI) and integrated discrimination improvement (IDI). This commentary reviews the development of such reclassification statistics along with more recent advances in our understanding of these measures. We show how the two‐category NRI and the IDI are affected by changes in the event rate in theory and in an applied example. We also describe the role of calibration and how it may be assessed. Finally, we discuss the relevance of the event rate NRI for clinical use. Copyright © 2017 John Wiley & Sons, Ltd.